(untitled) - Carroll, Paul (New York, 1994)
Throughout most of this century, IBM was a golden bulwark of the American economy. Hugely profitable and famously well managed, Big Blue was more than just a company; it was an international institution. But in the late 1980s, the legend unraveled. IBM fumbled an early lead in the personal computer business, with devastating, possibly irreparable consequences. Carroll, who covered IBM for seven years with the Wall Street Journal , breathes drama into this high-tech tale by focusing not on technological minutiae but on the human players, from fabled chairman Tom Watson Jr. to Microsoft wunderkind Bill Gates (who, more than anyone else, authored IBM's undoing). Although somewhat loosely structured, this work is a captivatingly well-reported piece. This is the first major book on an important chapter in American corporate history. Highly recommended.
Keywords: International business machines corporation,Computer industry; History,History; United states